THE SIMON KUZNETS'S INFLUENCE ON THE DEVELOPMENT OF ECONOMETRICS AND ENVIRONMENTAL ECONOMICS - O. Chernyak; O. Komashko (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка, 2014)
S. Kuznets's empirical and theoretical researches of the economical growth and economical development, made in 1940 – 1960th, became a main source for upgrading the econometrical models of those processes. The ideas of S. Kuznets gave a beginning for two outstanding directions of the applied literature. The first one deals with the Kuznets's cycles, that have approximately 20 years length period. The second direction appeared after the Kuznets's hypothesis about the unequal allocation of income in a process of economical growth. Kuznets made an assumption, that this inequality growth first and then rolls off. This dependence was named "Kuznets curve". An appearance of new works is caused by creation of new econometrical methods and models (panel data, nonstationarity) and by putting forward new theoretical explanations of the phenomenon. Similarly to the original Kuznets curve in the early 1990th "Environmental Kuznets curve" was suggested. After appearance of that concept plenty of econometrical researches were done. On our opinion, the Kuznets's scientific heritage includes great unsolved potential. The usage of this potential will promote a further progress of economical theory.